2003
DOI: 10.1038/sj.bjc.6601429
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation differentially affects substratum-dependent survival, adhesion, and invasion of glioblastoma cell lines

Abstract: Effects of ionising radiation on extracellular matrix (ECM)-modulated cell survival and on adhesion and invasion are not well understood. In particular, the aggressiveness of glioblastoma multiforme has been associated with tumour cell invasion into adjacent normal brain tissue. To examine these effects in more depth, four human glioblastoma cell lines (A-172, U-138, were irradiated on fibronectin (FN), Matrigel, BSA or polystyrene. Major findings of this study include a significantly increased survival of ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
76
3
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 51 publications
6
76
3
6
Order By: Relevance
“…Cell division is a highly regulated process that is modulated in response to adverse conditions including ionizing radiation [40,41]. Signaling via adhesion of integrins to laminin 5 is known to be involved in progression through the G1 phase of the cell cycle [32,33,42] and other integrin/ligand interactions in the G2/M transition [35,43]. Our data support adhesion-mediated regulation of the G2 phase through the integrin ligand laminin 5.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Cell division is a highly regulated process that is modulated in response to adverse conditions including ionizing radiation [40,41]. Signaling via adhesion of integrins to laminin 5 is known to be involved in progression through the G1 phase of the cell cycle [32,33,42] and other integrin/ligand interactions in the G2/M transition [35,43]. Our data support adhesion-mediated regulation of the G2 phase through the integrin ligand laminin 5.…”
Section: Discussionsupporting
confidence: 73%
“…However, it has been reported that in some cell lines, adhesion does not confer increased survival after DNA damage [43] and G2 arrest responses can occur without altering cell survival [55]. In our study, adhesion to laminin 5 did not influence cell survival in PrEC, PC3, and MCF10A cells exposed to ionizing radiation.…”
Section: Discussioncontrasting
confidence: 66%
“…For instance, x-ray irradiation increases expression of functional integrins β1 and β3 in glioma cell lines in a dose-dependent manner [8]. In lung adenocarcinoma A549 and SKMES1 cells, x-ray irradiation also induces expression of functional integrin β1 [9].…”
Section: Introductionmentioning
confidence: 99%
“…10,14,15 Further, increasing migration at low doses has been described, followed by a decrease at higher doses. 2,9 On the other hand, irradiation-induced reduction of migration and invasion was shown for colon carcinoma, glioblastoma and lung carcinoma 3,4,16 as well as reduction of plating efficiency in irradiated hepatocarcinoma and mouse mammary carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…The irradiation-induced impairment of cellular viability, proliferation and clonal survival was analyzed in many different tumor entities, among them were glioblastoma, non-small-cell lung cancer, colon carcinoma and melanoma. [2][3][4] The influence of irradiation on human melanoma cells was analyzed by Ristic-Fira and colleagues who found a dose-dependent decrease of cell proliferation 7 d after irradiation with gamma rays. 5 In a previous study we analyzed the impact of irradiation on mouse melanoma cells and also found decreased viability and proliferation, respectively, which persisted for at least two weeks.…”
Section: Introductionmentioning
confidence: 99%